TA'RĪB AS AN ARABIC MODERNIZATION AND THE SPIRIT OF NATIONALISM: A HISTORICAL STUDY OF ARABIZATION / TA’RIB SEBAGAI MODERNISASI BAHASA ARAB DAN SEMANGAT NASIONALISME: SEBUAH KAJIAN HISTORIS TENTANG ARABISASI - Muhammad Saiful Anam (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
This article aims to investigate the process of forming ta'rīb (Arabization) of foreign words into Arabic language and factors influencing the arabization process. The researcher used library research method with historical analysis. Research data sources were a number of literatures that is considered valid and credible. The result of study indicated that ta'rīb have began in the late 19th century and the ta’rib phenomenon that occur in Arabic was as a response to the development of civilization although there were pros and cons. Ta'rīb process of foreign words and terms into Arabic language was carried out in three ways, namely absorption, translation and formation of new words or terms. Absorption of words and terms was usually done by lexicographers, while the translation and formation of new words or terms were mostly done by language institutions. There were several factors that lead to the ta'rīb process, namely the influence of the power politics, science development carried out by scientists and writers, the influence of globalization, and the spirit of nationalism of Arab society.